Optimasi Kecepatan Potong Dan Kedalaman Pemakanan Terhadap Kekasaran Permukaan Baja St 40 Pada Proses Bubut CNC Menggunakan Response Surface Methodology - Afriadi, Muhammad; Subhan, Muhamad; Ary Wahyudie, Ilham; Yuliyanto, Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Optimal surface roughness results are the desired goal in the machining process on a CNC machine, the appropriate machining process variables must be adjusted in order to obtain an optimal workpiece surface roughness response. The research that has been carried out aims to determine the effect of variables on the surface roughness of the St 40 steel machining process in CNC machining and the optimal setting of the CNC machining process variable on the response value of the St 40 steel surface roughness. The machining process variables that are varied are cutting speed and depth of infeed. The optimization method used is the Response Surface Method. The experimental design was determined based on a 2-factor CCD. Experiments were carried out according to the experimental design of variable cutting speed with levels of 200 m/minute, 230 m/minute, and 260 m/minute and variable depth of ingestion with levels of 0.6 mm, 0.8 mm, and 1 mm to determine the optimal variable level. on the surface roughness of St 40 steel. The results showed that the influence of the variable cutting speed and depth of infeed did not significantly affect the surface roughness of St 40 steel and at the variable level optimization setting the minimum optimal value was obtained, namely at the cutting speed at 19.92 m/ minute and the depth of ingestion is at 5.58 mm and the resulting surface roughness value is smaller than 1,00 µm.